2012
DOI: 10.4236/ss.2012.33030
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mosquito-Net Cloths as Prosthesis in Inguinal Hernia Repair: An Experience in Southern Sudan

Abstract: Inguinal hernia is one of the commonest medical problems in Africa and the treatment via open repair is considered as one of the most affordable and secure procedures. In the industrialized countries, the gold standard treatment is represented by placing a prosthesis which is usually a mesh, made of alloplastic material, such as polypropylene. In developing countries, a piece of nylon mosquito-net without insecticide is a cheaper and safe alternative as prosthesis. This study shows the security of implant of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Our results are in line with earlier observational studies that found similar outcomes in terms of postoperative complications and hernia recurrence between patients undergoing groin hernia repair using a low-cost mesh and those undergoing the procedure using a commercial mesh. Our results are also in line with a large-scale clinical experience with low-cost mesh [15,22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are in line with earlier observational studies that found similar outcomes in terms of postoperative complications and hernia recurrence between patients undergoing groin hernia repair using a low-cost mesh and those undergoing the procedure using a commercial mesh. Our results are also in line with a large-scale clinical experience with low-cost mesh [15,22].…”
Section: Discussionsupporting
confidence: 90%
“…Kiss A et al [22] The researchers concluded that the easy use of analysed low-cost material and the demonstrated safety of these sterilised prostheses are two important factors that make them excellent solutions in poor and rural areas such as Southern Sudan.…”
Section: Klosterhalfen Et Al [9]mentioning
confidence: 99%